Analisis Kemampuan Ruang Terbuka Hijau (RTH) Publik Dalam Mereduksi Emisi Karbon Dioksida (CO2) Dari Kegiatan Transportasi Di Kecamatan Bangkinang Kota - Rezka Rahayu Febri; Aryo Sasmita; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The green open space is one of an effort in order to handling of the increasing the greenhouse gas emission, because green open space has an ability to absorbing the CO2 emission. The purpose of this research is to find out the CO2 emissions from transportation activities, knowing the ability of absorption of CO2 by the public’s green open space, analyze the level of absorption of CO2 by green open space from transportation activity, and to plan for the addition of public’s green open space in Bangkinang Kota district. The method in this research is calculate the value of CO2 emissions, counting the trees which has diameters more than 20 centimeter, and calculate the area of vegetation cover. The sufficiency of green open space was analyze and then compared the absorbing power of CO2 by trees with number of CO2 emissions that produced. Bangkinang Kota district is produced the CO2 emissions from transportation which is high enough as much as 32.884.770,640 kilograms CO2/year. While the ability of CO2 absorption by the public’s green open space in Bangkinang Kota district only 1.178.356,154 kilograms CO2/year. The result of analysis show that the public’s green open space in Bangkinang Kota district that viewed from absorbing CO2 emissions of transportation is still not enough with percentage is only about 3,59%. The absorbtion rate of public’s green open space is planned to reduce all CO2 emissions from transportation activities in Bangkinang Kota district is equal to 34.510.474,20 kilograms CO2/year.Keywords: Greenhouse Gas, Co2 Emissions, and Green Open Space